Profiling Murder Prisoners in Criminology Studies at Kedungpane Class 1 Correctional Institution in Semarang - Akbar, Faisal; Bakti, Aditama Esa; Hildayanti, Vinda Pramesta; Arya, Mohammad Bayu (Law Research Review Quarterly, 2020)
Murder is classified as a serious crime, because it takes a person's life and violates the most basic human right (right to life). This research tries to collect information in the form of the perpetrator’s personal data, what is the motive of the murder perpetrator, the motive, background and environment of a prisoner and tries to get information from prison officers about what are the parameters of an inmate who is ready to be released in social life and what efforts what the prison authorities do to restore the deviant behavior of a prisoner and direct them to return to acting according to the norms that exist in society and analyze all existing facts with theories from criminology. The research, which was conducted in the Kedungpane Correctional Institution Class I in Semarang, was intended to collect data, both from prisoners and prison officers. The research found several interesting facts about the perpetrator’s motive for killing were discovered. The research highlights if usually someone will kill someone because of revenge or economic pressure, labeling or labeling from the closest people also encourages the perpetrator to commit the crime of murder. Some of the sentences handed down to inmates can also be considered incompatible with their actions, so that the ruling party, who is the president, must make changes to several decisions on imposing criminal penalties as stated in the Criminal Code so that the law not only protects the community, but also provides true justice to the murderers.